MANAGEMENT IN THE SYSTEM OF PROFESSIONAL RETRAINING OF PEDAGOGICAL STAFF (Pedagogy of Higher and Secondary Education, 2004)
This article concerns the abilities of pedagogical management during the process of pedagogical training as one of the ways of professional readiness.